Detection of malaria parasites in laboratory infected Anopheles mosquitoes - Akter, Tangin (Dhaka University Journal of Biological Sciences, 2013)
Abstract not available Dhaka Univ. J. Biol. Sci. 22(2): 187-190, 2013 (July)